Dark Pools Off-Exchange Liquidity in an Era of High Frequency, Program, and Algorithmic Trading - Banks, Erik. (Global Financial Markets series, 2014)
This book deals with the topic of dark trading, or non-displayed, off-exchange trading execution. It discusses the development, importance and practice of dark equity trading in an environment dominated by high frequency, program, block and algorithmic trading, and considers its future prospects in a world of mobile capital and changing regulation.